Effect of dehydration methods on physico‐chemical and sensory qualities of restructured–dehydrated fish product. Issue 6 (24th March 2017) - Kumar, Anuj; Elavarasan, Krishnamoorthy; Kishore, Pankaj; Uchoi, Devananda; Mandakini Devi, Hanjabam; Ninan, George; Zynudheen, A. A.
Abstract: Development of restructured–dehydrated fish product enhances the shelf life as well as commercial value of fish. Along the similar lines, tiger tooth croaker ( Otolithes ruber ) mince was utilized in making restructured–dehydrated product (RDP). The effect of vacuum (VD), hybrid‐solar (SD), and fluidized bed drying (FBD) on proximate composition, bio‐chemical characteristics, and sensory acceptability of the RDPs was studied. Protein content of RDPs varied from 38.71 to 42.33%. The water activity of RDPs varied from 0.48 to 0.53, indicating shelf stability of RDPs. Lipid deterioration during drying was minimal as revealed by TBARS and FFA values. Rehydratability of FBD product was significantly ( p  ≤ 0.05) lower than others. Frying of RDPs yielded fish‐cracker like products. Fried VD product was sensorially more acceptable than others. The present study could pave the way for development of a new class of fish meat based products wherein low value fish meat are utilized. Practical applications: Fish meat is highly perishable and requires refrigerated and/or frozen storage. The restructured–dehydrated product provides a way to enhance the shelf life of fish meat. The low water activity associated with these products make them shelf stable. The RDPs could enhance the commercial value of fish meat. The RDPs obtained are highly convenient for preparation and could be consumed after frying or boiling or as an ingredient in fish curry.